Mumārasat al-Sulūk bi Minangkabau: Tarbīq al-Ta’ālim al-Islāmīyah ‘alā al-Thaqāfah al-Maḥallīyah - Sri Denti (Studia Islamika, 2004)
This article presents discussions about "suluk (mystic) rituals" in Minangkabau, which can be seen as a form of expression of Islamic rituals, in this context tariqah (Sufi order) practices, which have been integrated into local rituals and culture. It explains that the suluk tradition in Minangkabau developed in exclusive areas, in this context the hinterland or the area of Minangkabau where matrilineal traditions are still strong, not coastal areas with quite a high level of socialisation, because social interaction is quite significant.DOI: 10.15408/sdi.v11i2.605